THE RELATIONSHIP OF PARENTING A PARENT WITH TEMPER TANTRUMS IN CHILDREN OF PRESCHOOL AGE - Padang, Chaterina Banne; Ranteallo, Regina Reni; Sugiyanto, Sugiyanto (Universitas Islam Negeri Alauddin Makassar, 2021)
Temper tantrums are episodes of anger that on average are described as crying, screaming, but tantrums are also said to be extreme frustration, which looks like losing control characterized by violent or aggressive body movements such as throwing things away, rolling on the floor, banging heads , and stepped on the floor. The research objective was to determine the relationship between parenting style and temper tantrums in preschool children in the Mandetek area of the North Makale Health Center. The research design used in this research is a quantitative approach. The instrument (measuring instrument) in this study is a questionnaire which is the result of theory development and is arranged in the operationalization of the concept. The questions in the questionnaire use a Likert scale. The sample of this research is parents who have preschool age children who are in the Mandetek area of Puskesmas Makale Utara with a sample size of 43 parents. After the data was collected and processed using the Kolmogorov Simirnov statistical test with a significance α ≤ 0.05.